Assessment of Post Traumatic Stress Disorder and the Associated Socio Demographic Parameters of Road Traffic Accident Victims - Haque, Shayla; Sultana, Nihar (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Background: Road traffic accident (RTA) is a global trauma which can produce a traumatic stress with tremendous physical, social and psychological impairments to the victims. Post traumatic stress disorder (PTSD) is the most common mental disorders among the RTA victims. Objectives : To assess the PTSD among the RTA victims and the relationship between the socio demographic parameters of RTA victims with PTSD. Methods: This cross sectional study conducted among 202 RTA patients attended in the inpatient dept. of a specialized hospital in Dhaka city for one year duration. Data collected from these patients using a semi structured interview administered questionnaire and PTSD assessed by using Diagnostic and Statistical Manual-IV DSM-IV(PCL-S). The collected data were analyzed by using SPSS software (Version 21) and p < 0.05 considered as significant. Results: The mean age of RTA victims found 37.6 (±13.2) years, majority 57.4% belongs to 18-30 years age group. Out of 202 RTA patients 41.1% developed PTSD having e”51 score in Diagnostic and Statistical Manual-IV DSM-IV (PCL-S) checklist. Among the socio demographic parameters age and occupation were significantly associated with the PTSD; whereas education, family income, sex were not associated significantly with PTSD. Conclusion: This study found a high magnitude of PTSD among RTA victims. J Bangladesh Coll Phys Surg 2023; 41: 22-26